2023
DOI: 10.3389/fpsyg.2023.1027349
|View full text |Cite
|
Sign up to set email alerts
|

Multiple teams, multiple projects, multiple groups at the intersection of (multiple) research fields: A bibliometric study

Abstract: Multi-teaming is a concept studied across a variety of disciplines. While using a bibliometric approach on 255 research papers extracted from Web of Science, we aimed to depict the architecture of the multi-teaming concept across academic disciplines and time. Results of citation, co-citation and bibliographic coupling analyses identified four major fields looking at the concept of multi-teaming. The fields emerged over time from fragmentation to integration and acknowledging similarities. We identify gaps and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 116 publications
1
7
0
Order By: Relevance
“…With teams established as a core and versatile unit for organizing work, this organization proceeded by introducing organizational constructs to aggregate multiple teams. The main reason for this organizational design was the pursuit of agility (Bundtzen and Hinrichs, 2021) and optimal use of human resources within the organization (Meslec et al, 2023). Based on the results of our study, we infer that this setup aimed toward agility also brought resilience.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…With teams established as a core and versatile unit for organizing work, this organization proceeded by introducing organizational constructs to aggregate multiple teams. The main reason for this organizational design was the pursuit of agility (Bundtzen and Hinrichs, 2021) and optimal use of human resources within the organization (Meslec et al, 2023). Based on the results of our study, we infer that this setup aimed toward agility also brought resilience.…”
Section: Discussionmentioning
confidence: 68%
“…Modern organizations increasingly rely on teams and multiteam systems to perform effectively and stimulate autonomous work (Meslec et al, 2023), and they tend to change their leadership approaches from hierarchical forms to more participative and empowering ones. Leadership support is a key antecedent for the effectiveness of organizational teams as it impacts job crafting and is a key job resource for employees (Cortellazzo et al, 2019;Fodor et al, 2021;Tummers and Bakker, 2021).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Taken together, our review advances MTM theory by providing a nuanced understanding of MTM's influence on effectiveness. Earlier reviews discussed the MTM-effectiveness relationship within a broader framing of determinants, outcomes, and experiences of multiteaming, while focusing on boundary conditions to make sense of the observed complex relationship (Margolis, 2020) or identified the vast array of disciplines interested in studying MTM, while highlighting some of the key theories in MTM research through a bibliometric overview (Meslec et al, 2023). We analyze the MTM literature through a team lens (Hollenbeck et al, 2012;Mathieu et al, 2017) sion that identified two broad perspectives to explain MTM outcomes -namely, the social network and attention perspec tive and the resource and demands perspective -to delineate four categories of processes that account for how MTM's influence occurs.…”
Section: Discussionmentioning
confidence: 99%
“…(2011) proposed the countervailing consequences of MTM for individual and team learning and productivity. Scholars across disciplines ranging from Social Psychology to Industrial Engineering and Computer Science have taken an interest in MTM (Meslec et al., 2023). Initial work studied the effect of specific MTM structures such as employees' number of concurrent teams (i.e., MTM number) on individual and team effectiveness (e.g., Bertolotti et al., 2015; Chan, 2014; Cummings & Haas, 2012).…”
Section: Intoroductionmentioning
confidence: 99%
See 1 more Smart Citation